Pharmacokinetics and outcome of high-dose melphalan followed by autologous stem cell transplantation in dialysis-dependent patients with multiple myeloma - Rabea Mecklenbrauck; Bernhard M.W. Schmidt; Heike Bähre; Annamaria Brioli; Arnold Ganser; Florian H. Heidel; Felicitas Thol (Leukemia Research Reports)
High-dose melphalan followed by autologous stem cell transplantation (ASCT) remains the standard of care for fit patients with multiple myeloma (MM). However, individuals who are dependent on hemodialysis are frequently excluded from ASCT. Recommendations on chemotherapy dosing and hemodialysis scheduling vary in literature and definite conclusions are impeded by the heterogeneity of cohorts.We aimed to evaluate the safety and efficacy of ASCT in patients with MM and end-stage renal disease and to examine the pharmacokinetics of melphalan on a fixed schedule of melphalan infusion and hemodialysis.The outcome of 13 patients undergoing ASCT while being on hemodialysis between 2000 and 2022 was retrospectively analysed and compared to matched hemodialysis-independent patients. Melphalan plasma concentrations were measured in 4 hemodialysis-dependent and 5 independent patients.Plasma concentrations of hemodialysis-dependent patients were comparable to hemodialysis-independent patients with a 6-hour interval between melphalan infusion and hemodialysis (p = 0.9). The rate of immediate side effects of high-dose melphalan was significantly higher in 13 dialysis-dependent patients compared to 47 matched controls despite not having prolonged neutropenia (p = 0.9). Overall survival both from d0 of ASCT and diagnosis was comparable (p = 0.33 and p = 0.17, respectively).Thus, adopting the proposed schedule and management of immediate side effects make ASCT a safe option for myeloma patients with end-stage renal disease.